2011
DOI: 10.1371/journal.pone.0018555
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Buccal Cavity Mucus in Female Tilapia Fish (Oreochromis spp.): A Comparison between Parental and Non-Parental Fish

Abstract: Mouthbrooding is an elaborate form of parental care displayed by many teleost species. While the direct benefits of mouthbrooding such as protection and transportation of offsprings are known, it is unclear if mouthbrooding offers additional benefits to embryos during incubation. In addition, mouthbrooding could incur negative costs on parental fish, due to limited feeding opportunities. Parental tilapia fish (Oreochromis spp.) display an elaborated form of parental care by incubating newly hatched embryos in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Intact haemoglobin and its fragments isolated from human and Alligator mississippiensis have been shown to possess a broad spectrum of antimicrobial activity (Hodson & Hirsch 1958;Parish, Jiang, Tokiwa, Berova, Nakanishi, McCabe, Zuckerman, Xia & Gabay 2001). (Iq & Shu-Chien 2011), in human cervical mucus (Panicker et al 2010) and in olfactory cleft mucus (D ebat, Eloit, Blon, Sarazin, Henry, Huet, Trotier & Pernollet 2007). Haemoglobin subunits (alpha and beta) have also been identified in the normal buccal cavity mucus in female Oreochromis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Intact haemoglobin and its fragments isolated from human and Alligator mississippiensis have been shown to possess a broad spectrum of antimicrobial activity (Hodson & Hirsch 1958;Parish, Jiang, Tokiwa, Berova, Nakanishi, McCabe, Zuckerman, Xia & Gabay 2001). (Iq & Shu-Chien 2011), in human cervical mucus (Panicker et al 2010) and in olfactory cleft mucus (D ebat, Eloit, Blon, Sarazin, Henry, Huet, Trotier & Pernollet 2007). Haemoglobin subunits (alpha and beta) have also been identified in the normal buccal cavity mucus in female Oreochromis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, comparative proteomic analysis shown that GAPDH was associated with the high susceptibility of channel catfish ( Ictalurus punctatus ) after immersion exposure to Edwardsiella ictaluri (Booth and Bilodeau‐Bourgeois, ), and GAPDH was also identified as up‐regulated protein in the buccal cavity mucus of parental tilapia ( Oreochromis spp.) (Iq and Shu‐Chien, ). Therefore, GAPDHs may have activities involved in the immune function or cellular stress responses in fish (Booth and Bilodeau‐Bourgeois, ; Iq and Shu‐Chien, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Iq and Shu‐Chien, ). Therefore, GAPDHs may have activities involved in the immune function or cellular stress responses in fish (Booth and Bilodeau‐Bourgeois, ; Iq and Shu‐Chien, ). The mRNA expression of GAPDH2 was significantly up‐regulated in the liver of rockbream ( Oplegnathus fasciatus ) against the bacterial infections, which suggests that fish GAPDH2 may also be potentially involved in immune responses (Cho et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Parents of the caecilian amphibian Boulengerula taitanu modify their skin, which is eaten by their offspring using specialised teeth (Kupfer et al, 2006), and it has been proposed that the fry of mouth-brooding tilapia, e.g. Oreochromis spp., ingest mucus containing nutrients from the buccal cavity of their parents (Kishida and Specker, 2000;Iq and Shu-Chien, 2011). Other non-mammalian examples exist where animals are fed a nutritive secretion pre-parturition.…”
Section: Introductionmentioning
confidence: 99%